Wear property improvement by short carbon fiber as enhancer for rubber compound. (August 2019) - He, Qiang; Zhou, Yangjing; Qu, Wenhong; Zhang, Yong; Song, Lei; Li, Zhanjun
Abstract: Blending technique is applied to prepare nitrile rubber/short carbon fiber (NBR/SCF) composite. The friction and wear properties of NBR and NBR/SCF are investigated by wear surface analysis via three-dimensional(3D) topography measurement and scanning electron microscopy (SEM). Results show that the hardness of NBR/SCF composite increases by 22.7% compares to NBR. At different test forces, the friction coefficient of two rubbers increases at first, then decreases to a stable level over time. The mass and volume loss after wear, as well as wear depth of NBR are larger than that of NBR/SCF composite. SEM images show that dispersed SCFs create framework in the vulcanization process, which alleviates the wear degree of the surface. In addition, the C and O content on the surface of NBR/SCF composite are higher than that of NBR rubber, further confirms the improvement of friction and wear properties brought by SCFs. Highlights: Blending technique is applied to prepare nitrile rubber/short carbon fiber (NBR/SCF) composite. The hardness of NBR/SCF composite increases by 22.7% compares to NBR. The mass after wear are larger than that of NBR/SCF composite. SEM images show that dispersed SCFs create framework in the vulcanization process. The C and O content on the surface of NBR/SCF composite are higher than that of NBR rubber.